2020
DOI: 10.1038/s41419-020-2705-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ETS1 in gastric epithelial cells positively regulate inflammatory response in Helicobacter pylori-associated gastritis

Abstract: Gastric epithelial cells (GECs) provide the first point of contact of the host by Helicobacter pylori (H. pylori), and the interaction between H. pylori and GECs plays a critical role in H. pylori-associated diseases. Aberrant expression of transcription factors (TFs) contributes to the pathogenesis of inflammatory disorders, including H. pylori-associated gastritis. ETS (E26 transformation specific) transcription factor family is one of the largest families of evolutionarily conserved TFs, regulating critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…H. pylori infection induces a systemic Th-17 inflammatory response, which plays an essential role in the pathophysiology of SLE [ 63 , 64 ]. Moreover, H. pylori can increase the expression of ETS1, through the CagA-activated NF-κB pathway [ 65 ], a negative regulatory transcription factor for Th17 cell and B cell differentiation involved in the pathogenesis of SLE [ 66 ]. Therefore, further investigations are required to comprehend the role of H. pylori in these pathways and the risk of SLE.…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…H. pylori infection induces a systemic Th-17 inflammatory response, which plays an essential role in the pathophysiology of SLE [ 63 , 64 ]. Moreover, H. pylori can increase the expression of ETS1, through the CagA-activated NF-κB pathway [ 65 ], a negative regulatory transcription factor for Th17 cell and B cell differentiation involved in the pathogenesis of SLE [ 66 ]. Therefore, further investigations are required to comprehend the role of H. pylori in these pathways and the risk of SLE.…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The gastritis induced by it is chronic and can develop into atrophic gastritis, intestinal metaplasia, and dysplasia. At the same time, cyclooxygenase-2 (COX-2), an important factor in Helicobacter pylori-associated gastritis, angiogenesis, and inhibition of apoptosis in gastric carcinoma are evidently related to infiltration [6][7][8]. Recently, studies have shown that COX-2 expression is upregulated in GC as well as in precancerous lesions and in Helicobacter pylori-induced inflammation, suggesting that COX-2 may play an important role in gastric carcinogenesis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vitro find that Helicobacter pylori was correlated with an upregulation of the expression of COX-2 mRNA/protein 2 in gastric cancer (GC) cell line. Therefore, the relatively early role of COX-2 in gastric carcinogenesis makes it an attractive target for cancer chemoprevention [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the FEAR pathway appears to both predate and be distinct from, the IFN response. However, only recently was ETS-1 implicated in the host response to microbial infection in bacterial studies where its expression was shown to induced by infection to activate proinflammatory gene expression 30 . Our data indicate that ETS-1 also restricts virus replication and is induced by virus infection in an hSpt16 SUMO /FACT-dependent manner.…”
Section: Discussionmentioning
confidence: 99%